Zur Auflösung der Nulläquivalenz im nominalen Bereich bei der Translation aus dem Deutschen ins Polnische - Grabarek, Józef (Studia Germanica Posnaniensia, 2018)
The subject of the author's considerations is the phenomenon of the so called zero equivalence and the way of overcoming it in the process of translating of German texts into Polish and vice versa. The author investigated in particular the specificity of rendering in both languages the multi-word names of organizations and the like.